Eczematous reaction to IVIG for the treatment of dermatomyositis - J. Berk-Krauss; K. Lee; K.I. Lo Sicco; T.N. Liebman (Wolters Kluwer, 2018)
The use of high-dose intravenous immunoglobulin (IVIG) is an accepted therapy for patients with refractory dermatomyositis. Cases of eczematous reactions to IVIG have been reported in the literature, but to our knowledge, none in patients being treated for dermatomyositis. We report on the cases of two female patients with refractory dermatomyositis who developed pruritic, scaly pink plaques after receiving high-dose IVIG. This diffuse eczematous skin reaction to high-dose IVIG is a rare adverse event that most often occurs days after administration of therapy. Practitioners should be aware of this entity because the eczematous eruption may be extensive and can commonly worsen with subsequent re-exposure to IVIG. Keywords: intravenous immunoglobulin, dermatomyositis, drug reaction, eczematous skin eruption, immunomodulators, systemic steroid medications